PROGRAMMABLE BASKETBALL SHOOTING MACHINE: TRAINING BENEFITS - Skachkov, D.V.; Naboychenko, E.S.; Kormyshev, V.M.; Yang, K.S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to theoretically analyze and practically test benefits of a programmable basketball shooting machine for technical skills training in basketball groups. Methods and structure of the study. The study included a basketball-shooting-machine-assisted training experiment on a sample of the 17-23-year-old basketball players (n=28) of different skill levels. We split them up into Experimental and Control Groups (EG, CG) of 14 people each. The skill levels in the groups were as follows: unskilled non-competing athletes (n=2 in each group); athletes with basic skill sets but no experience in school/ Youth Sports School competitions (n=4 in each group); fairly skilled athletes trained at the Youth Sports School (n=4 in each group); and highly-skilled experienced Student Basketball Association competitors (n=4 in each group). Results and conclusion. The training experiment with the pre-versus post-experimental physical fitness/ technical fitness / special endurance tests and analyses showed the basketball-shooting-machine-assisted training model being highly beneficial as it facilitates individual progress in many aspects with a special emphasis on the individual weaknesses and technical skills improvement barriers, opportunities and creative resource mobilizing emphases – both in the pre-seasonal training and competitive periods.